2014
DOI: 10.1038/ncomms6524
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor 3A controls interneuron migration into the neocortex

Abstract: Neuronal excitability has been shown to control the migration and cortical integration of reelin-expressing cortical interneurons (INs) arising from the caudal ganglionic eminence (CGE), supporting the possibility that neurotransmitters could regulate this process. Here we show that the ionotropic serotonin receptor 3A (5-HT3AR) is specifically expressed in CGE-derived migrating interneurons and upregulated while they invade the developing cortex. Functional investigations using calcium imaging, electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 59 publications
4
94
0
Order By: Relevance
“…Interestingly, long-lasting alteration in the positioning of reelin+ cortical interneurons was reported. This suggests that 5-HT 3A activation acts as a migratory signal for CGE-derived interneurons and alters definitively the positioning of their subpopulation [189]. A similar conclusion was suggested using SERT:KO animals that showed a specific increase in the migratory speed and positioning of VIP+ interneurons [92].…”
Section: Serotonin and Neuronal Migrationsupporting
confidence: 63%
“…Interestingly, long-lasting alteration in the positioning of reelin+ cortical interneurons was reported. This suggests that 5-HT 3A activation acts as a migratory signal for CGE-derived interneurons and alters definitively the positioning of their subpopulation [189]. A similar conclusion was suggested using SERT:KO animals that showed a specific increase in the migratory speed and positioning of VIP+ interneurons [92].…”
Section: Serotonin and Neuronal Migrationsupporting
confidence: 63%
“…However, due to the wide expression of those proteins, both in GABAergic interneurons and many other cells, as well as the global nature of the mouse mutants employed, it remains unclear to which extent the effects observed were cell-autonomous or caused by other cortical abnormalities. For GABAergic interneurons derived from the CGE, the serotonin receptor 3A was recently found to play a role in cortical plate invasion (Murthy et al, 2014). Here we showed that MGE-derived interneurons can reach the neocortex in normal numbers in the absence of TCAs, indicating that they do not require this axonal tract for tangential migration from the ventral telencephalon nor for tangential dispersion through the subplate and IZ.…”
Section: Discussionmentioning
confidence: 99%
“…To understand how CGE-derived INs reach their multiple targets, we used the 5HT3aR-GFP mouse transgenic line, previously reported to label the totality of CGE-derived cortical INs in embryos and in adult mice (Inta et al, 2008;Lee et al, 2010;Murthy et al, 2014;Rudy et al, 2011;Vucurovic et al, 2010). Embryonic day (E) 11.5 to E18.5 5HT3aR-GFP + brains were cut in a horizontal plane allowing an overview of all three GE structures in one section (Fig.…”
Section: Identification Of Two Novel Tangentially Cge-derived Paths Imentioning
confidence: 99%
“…Whereas COUP-TFII acts mainly in directing CGE-derived cells to the caudal migratory stream (CMS) (Cai et al, 2013;Kanatani et al, 2008;Yozu et al, 2005), COUP-TFI is required for the correct balance between MGE-and CGE-derived INs in the developing neocortex (Lodato et al, 2011b), but its role in migration is less known. 5HT3aR is expressed in migrating and mature CGE-and POA-derived cells (Lee et al, 2010;Vucurovic et al, 2010) and is cell-autonomously required for the migration and positioning of RLN + INs in the neocortex (Murthy et al, 2014). Finally, SP8 and PROX1 are transcription factors expressed principally in subpopulations of lateral ganglionic eminence (LGE)/CGE-derived cortical INs (Ma et al, 2012;Rubin and Kessaris, 2013;Rudy et al, 2011) and a recent report has demonstrated a crucial role for PROX1 in the embryonic and postnatal acquisition of CGE-derived cortical IN properties (Miyoshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation